An Effective Approach for Endocrine Dynamic Function Tests Workflow and Reporting Using Cerner Millennium®. (28th October 2021) - Asinas, J M; Khaiwi, W; Miller, A; Newland, P
Abstract: Introduction/Objective: Endocrine dynamic function testing (DFT), also known as hormone stimulation tests, are indispensable tools in the endocrine practice. Common pitfalls of ineffective testing and misdiagnosis are due to incorrect sample recordings, delay in sample collections and disorganized or confusing result presentation. Clinical and laboratory data deserves careful attention and discrepancies must be reviewed by a clinical biochemist before releasing results for proper patient diagnosis. The main objective of this Cerner DFT project is to design and implement Cerner Millennium applications for effective management and organized result reporting of hospital-wide DFT protocols. Methods/Case Report: The DFT Cerner workflow is uniquely designed in-house and known as a pioneer build for Cerner Millenium. The design involves the use of Cerner Discern Analytics 2.0 and clinical modules to complete such a complex build. Five DFT panels are defined as care-sets with specific hormone discrete task assays (DTA). For each care-set, an 'order sentence' is created to produce the order priority rules. The DFT panels can only be requested as future orders in PowerChart and activated by the medical staff upon collection of the baseline sample. On Cerner PathNet, results are pre-verified by the medical technologists then auto-filtered in the clinical Review Queue (RQ) module for final verification and addition of comments by the biochemistry consultant. A word processing template is used to collate the results and present the summary of the DFT report where standardized canned comments are added using pre-defined codes. Results (if a Case Study enter NA): See Conclusion Section Conclusion: The Cerner DFT project mproves the diagnosis and treatment of patients with hormone disorders. Before, there was a danger of misdiagnosis when samples are individually requested producing separate reports with no organized presentation. Report comments from the clinical biochemist consultant also served as good diagnostic guidance. This quality initiative has definitely improved the previous and long term issues of endocrine dynamic function tests.